Encapsulation technology in the food area: A review (Research, Society and Development, 2021)
The encapsulation technology has been advancing in recent years and has entered the various industrial segments by protecting substances (active agents) from deleterious effects that cause the loss of its function. It is based on an active agent protection by conditioning it in a shell produced by polymers. In the food sector, encapsulated substances can be found incorporated into the food matrix or as part of the industrial processes dynamics. The objective of this work consisted of a bibliographic survey, addressing the formation aspects, characterization and encapsulated materials application in the food area. The conceptualization of the technological emergence of encapsulation, the main methods for the particulate’s formation: physical, chemical, physical-chemical and those emerging in the study area were elucidated. The most explored active agents in the food sector were also presented, addressing their applications and innovative proposals, taking into account what this generates for future perspectives for the encapsulation technique, which among other purposes, provides better application to substances that have difficulties in commercialization. due to the high susceptibility to extrinsic factors that cause its deterioration. Thus, it is necessary to encourage the application studies to be further explored and that this is reflected in solutions that allow scaling at an industrial level.